The effect of slope aspect on vegetation attributes in a mountainous dry valley, Southwest China - Jie Yang (Nature Portfolio, 2020)
Abstract Slope aspect plays a critical role in influencing vegetation pattern in semiarid area. The dry valleys of the Hengduan Mountains Region, southwestern China, are striking geographical landscape, suffering from severe ecological degradation. Here, we comprehensively investigated how slope aspect affects vegetation attributes in one of these valleys- the dry valley in the upper reaches of Min River. Three sites were selected along the valley and we quantitively examined the vegetation difference between slope aspects at the whole valley scale and each site level. We found significant vegetation differences between slope aspects in species composition, vegetative structure, and biodiversity pattern, which were in accordance with the observed significant difference in soil nutrient. Generally, north-facing slopes are associated with higher biomass, coverage and height, and species diversity than south-facing slopes. We also found between-aspect differences varied among the study sites, resulting in increased biomass, height, and β diversity differences, decreased density and coverage differences, and opposite trend observed in α diversity at relatively wet site. In conclusion, slope aspect had significant effect on vegetation attributes, which was significantly influenced by local climate (aridity) in terms of both strength and direction depending on the specific attributes investigated.